ANALISIS FAKTOR YANG MEMPENGARUHI PENYERAPAN TENAGA KERJA PROVINSI NUSA TENGGARA BARAT - Muhammad Rafi'i Sanjani; Indah Fitriana Sari (Politeknik Bisnis Indonesia, 2024)
Unemployment in West Nusa Tenggara Province is still quite high which is the reason people living in the area decide to migrate. There are several factors that cause these people to migrate, including a high minimum wage rate, a large number of companies, a good economy. A good economic level can be seen from the high and low unemployment rate in the area. The high and low unemployment depends on the high and low labor force absorbed. In addition, there are factors that cause low employment including GDP, HDI, salary minimum wage, and investment. This research was conducted with the aim of determining the effect of Gross Regional Domestic Product (GRDP), Human Development Index (HDI), salary minimum wage (UMK), and investment on labor absorption in West Nusa Tenggara Province in 2017-2020. In this study for GRDP variables include production, HDI includes education, minimum wage includes MSEs and investment variables include Domestic Investment (PMDN) This study uses a type of quantitative research with secondary data obtained from the Central Statistics Agency (BPS) of West Nusa Tenggara Province and the Manpower and Transmigration Office. The data collection method used is a documentation technique, the collected data is analyzed using multiple regression equations using the Eviews 12 program.